Silicon and tanzania guinea grass tolerance to stress by copper toxicity - Vieira Filho, Leandro Otávio (2018)
Whist copper (Cu) is an essential element for plants, when this element is present in excess quantities it can cause irreversible damage. This metal induces excessive production of reactive oxygen species (ROS), which damages organelles causing dysfunction. A possible means for the promotion of metal tolerance in plants is the adition of the element silicon (Si). The current study was conducted with the aim of evaluating the role of Si (0, 1 and 3 mmol L-1) on the morphologic, nutritional, metabolic and physiological responses of Panicum maximum cv. Tanzania under different Cu rates (0.3, 250, 500 and 750 μmol L-1). The grass was grown in a greenhouse under hydroponic conditions for two growth periods (33 and 30 days). Thirteen days after sowing, the seedlings were transplanted to a nutrient solution and supplied just with the Cu rate of 0.3 μmol L-1 and the set Si rates for 25 days. The remaining Cu rates were only added for a seven day period during the first growth stage. The second harvest took place 31 days after the first harvest. The experiment had six randomized blocks: three for yield, morphology and nutritional analyses and three for metabolic and physiological analyses. Plant yield, morphology and metabolic parameters were quantified in shoots and roots. Chlorophyll content index (SPAD values) and gas exchange parameters were determined in diagnostic leaves (DL), and Cu and Si concentrations were analysed from the DL and roots. The calculation of Cu and Si contents took into account the whole plant biomass. Plants exposed to Cu rates above 0.3 μmol L-1 showed low values of plant yield, morphologic parameters and SPAD, in both growth periods. Silicon supplied plants showed lower Cu concentration and content, and higher values of plant yield, morphlogic parameters and SPAD than the ones with no Si application. Silicon concentration and content were higher in plants exposed to excess Cu compared to those exposed to the control rate (0.3 μmol L-1). Gas exchange parameters in plants of the first growth were positively affected by Si supply and negatively affected by Cu rates. In the second growth, an eustress event was observed, in which plants exposed to stressing rates of residual Cu showed the highest values of gas exchange parameters and the lowest values of stress indicators. The activities of antioxidant enzymes were reduced with the increment in Cu rates. Silicon supply resulted in an increment in superoxide dismutase (SOD) activity. Tanzania guinea grass supplied with Si was able to better deal with Cu toxicity, showing increases in plant yield, morphologic and gas exchange parameters. Silicon supplied plants reduced their absorption of Cu and consequently, plants exposed to high Cu rates were still able to produce considerable biomass in the regrowth.